Dextrose saline compared with normal saline rehydration of hyperemesis gravidarum a randomized controlled trial - Tan, P.C.; Norazilah, M.J.; Omar, S.Z. (2013)
OBJECTIVE: To compare 5 dextrose-0.9 saline against 0.9 saline solution in the intravenous rehydration of hyperemesis gravidarum. METHODS: Women at their first hospitalization for hyperemesis gravidarum were enrolled on admission to the ward and randomly assigned to receive either 5 dextrose-0.9 saline or 0.9 saline by intravenous infusion at a rate 125 mL/h over 24 hours in a double-blind trial. All participants also received thiamine and an antiemetic intravenously. Oral intake was allowed as tolerated. Primary outcomes were resolution of ketonuria and well-being (by 10-point visual numerical rating scale) at 24 hours. Nausea visual numerical rating scale scores were obtained every 8 hours for 24 hours. RESULTS: Persistent ketonuria rates after the 24-hour study period were 10 of 101 (9.9) compared with 11 of 101 (10.9) (P>.99; relative risk 0.9, 95 confidence interval 0.4-2.2) and median (interquartile range) wellbeing scores at 24 hours were 9 (8-10) compared with 9 (8-9.5) (P=.73) in the 5 dextrose-0.9 saline and 0.9 saline arms, respectively. Repeated measures analysis of variance of the nausea visual numerical rating scale score as assessed every 8 hours during the 24-hour study period showed a significant difference in favor of the 5 dextrose-0.9 saline arm (P=.046) with the superiority apparent at 8 and 16 hours, but the advantage had dissipated by 24 hours. Secondary outcomes of vomiting, resolution of hyponatremia, hypochloremia and hypokalemia, length of hospitalization, duration of intravenous antiemetic, and rehydration were not different. CONCLUSIONS: Intravenous rehydration with 5 dextrose-0.9 saline or 0.9 saline solution in women hospitalized for hyperemesis gravidarum produced similar outcomes.